STUDI IMPLEMENTASI MANAJEMEN KURIKULUM BERBASIS KECAKAPAN HIDUP (LIFE SKILLS) SISWA SD IT AL-FITRAH BINJAI - Munajad . (Jurnal Mutiara Pendidikan Indonesia, 2019)
This study aims to analyze the curriculum management of life skills of students in SD IT Al-Fitrah Binjai, starting from the planning, implementation, and evaluation processes. This research is a quantitative descriptive study, by taking the location of research at SD IT Al-Fitrah Binjai. Data collection techniques using observation, interviews, and documentation. The results showed that: (1) life skills curriculum management planning, including determining the education of skills to be carried out, conducting socialization, setting goals, distributing questionnaires, determining the time of implementation, selected skills education curriculum, preparing infrastructure; (2) the implementation of the development of students' life skills programs is divided into four main things, namely reorienting learning by integrating life skills programs through curricular, extracurricular and intracuricular activities; (3) the evaluation of the education program is in accordance with the target vision, mission and goals through evaluation per semester conducted by all the board of teachers together with the headmaster of madrasas and annual evaluations carried out by the headmaster, the madrasah committee found that the application of life skills-based curriculum in primary schools was not yet optimally implemented.